2012
DOI: 10.1016/j.jksues.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of performance measures of flexible manufacturing system

Abstract: Flexible manufacturing system (FMS) is a highly integrated manufacturing system. The relation between its components is very complex. The mathematical programming approaches are very difficult to solve for very complex system so the simulation of FMS is widely used to analyze its performance measures. Also the FMS components are very sophisticated and costly. If FMS has to be implemented then it is better to analyze its results using simulation which involves no loss of money, resource and labor time. As a typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…A recent survey was conducted to establish the problems in today’s layout planning process and it was found that graphical tools are able to create a more efficient and attractive environment that can replace existing planning processes 37 . Since flexible manufacturing system (FMS) is a system that integrates its elements tightly, the relation between them is often hard to compute 38 . Therefore, there is a demand for an analysis method that avoids any substantial loss in labour time, money, and resources.…”
Section: Layout Planningmentioning
confidence: 99%
“…A recent survey was conducted to establish the problems in today’s layout planning process and it was found that graphical tools are able to create a more efficient and attractive environment that can replace existing planning processes 37 . Since flexible manufacturing system (FMS) is a system that integrates its elements tightly, the relation between them is often hard to compute 38 . Therefore, there is a demand for an analysis method that avoids any substantial loss in labour time, money, and resources.…”
Section: Layout Planningmentioning
confidence: 99%
“…Elam et al (2010) explained about how to process, decide, count, assign, run, replicate, verify and validate model along with input-output analysers. El-Tamimi et al (2012) used Awesim simulation software for modelling the Assembly line. Simulation and design of experiments (DOE) was also carried for experimental study of optimising metal cutting line in press work (Jimeneez et al, 2012).…”
Section: Literature Surveymentioning
confidence: 99%
“…The waiting time of the parts in queue and the task distributions were taken as performance criterions. El Tamimi et al [5] have studied another concept and implementation of the Petri nets for measuring and analysis of FMS performance. The system has been modeled with simulation.…”
Section: Researches Using Petri Networkmentioning
confidence: 99%